2017
DOI: 10.3892/ijo.2017.3985
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated connexin32 promotes EMT through the Wnt/β-catenin pathway by targeting Snail expression in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the common malignances in the world and is associated with high mortality and poor prognosis, partly due to early invasion and metastasis. Cx32 has been indicated to be involved in the progression of many cancers including HCC, but its relationship with tumor invasion and metastasis is still controversial. In the present study, the downregulated Cx32 in HCC tissue was found negatively correlated with histological grade and lymph node metastasis. Cx32 regulated HCC migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 31 publications
(54 reference statements)
3
34
0
1
Order By: Relevance
“…mRNA levels showed that alteration of DEPDC1 expression significantly changed the expression of most of the selected genes in the SMCC‐7721 cells (Figure D), including NR4A2, SEPP1, EDN2, LYPD3, MMP9, WNT6, RAC2, WNT1, PTCH1 and CTNNB1. The oncogenic function of RAC2, NR4A2, MMP9 WNT1, PTCH1 and CTNNB1 has been reported in HCC . These results indicated that DEPDC1 may activate specific oncogenic signal pathways to promote HCC cell proliferation and metastasis.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…mRNA levels showed that alteration of DEPDC1 expression significantly changed the expression of most of the selected genes in the SMCC‐7721 cells (Figure D), including NR4A2, SEPP1, EDN2, LYPD3, MMP9, WNT6, RAC2, WNT1, PTCH1 and CTNNB1. The oncogenic function of RAC2, NR4A2, MMP9 WNT1, PTCH1 and CTNNB1 has been reported in HCC . These results indicated that DEPDC1 may activate specific oncogenic signal pathways to promote HCC cell proliferation and metastasis.…”
Section: Resultsmentioning
confidence: 75%
“…The oncogenic function of RAC2, NR4A2, MMP9 WNT1, PTCH1 and CTNNB1 has been reported in HCC. [17][18][19][20][21][22] These results indicated that DEPDC1 may activate specific oncogenic signal pathways to promote HCC cell proliferation and metastasis.…”
Section: Gene Set Enrichment Analysis Of Depdc1associated Signalingmentioning
confidence: 85%
“…Yang Y et al [104] found that inhibition of Connexin 32 (Cx32) upregulates Snail expression via activation of Wnt/β-catenin signaling in Hepatocellular carcinoma (HCC). Moreover, with decreased expression of Cx32 and a reduction in E-cadherin, higher Snail expression and nuclear accumulation of β-catenin was observed in HCC tissues.…”
Section: Snailmentioning
confidence: 99%
“…Excluding Cx32, one of the most efficient regulators of Snail is GSK-3β. Many signaling pathways mediated by growth factors regulate the function of Snail via GSK-3β, which is also involved in the regulation of the Wnt pathway [97,103,104].…”
Section: Snailmentioning
confidence: 99%
“…TGF‐β is considered the pivotal factor in inducing EMT during development, cancer and other pathological conditions. In some epithelial cell lines cultured in vitro, EMT can be induced by TGF‐β stimulation alone; furthermore, EMT is mediated by the Notch, Wnt/β‐catenin and integrin signalling pathways . Therefore, the regulation of EMT has been considered a therapeutic strategy to prevent the occurrence of ASC and PCO and to reduce the incidence of postoperative complications …”
Section: Introductionmentioning
confidence: 99%